Preservation of Javanese Cultural Lexicon in the English Translation of the Collection of Short Stories by Ahmad Tohari - Tri Septa Nurhantoro (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
Indonesian literature is rich with cultural nuance expressed by an author in his/her works. Being translated into world lingua franca would make the literary work read by more people, but surely, it is challenging, as a translator must apply the most appropriate translation strategies. Senyum Karyamin is one of Indonesian literary works that represent local culture and has been translated into English. Based on the analysis, in translating 122 Javanese cultural lexicons in Senyum Karyamin, a translator applied 7 strategies, namely: transference (34 data, 27.87%), omission (9 data, 7.37%), descriptive equivalence (19 data, 15.58%), cultural equivalence (25 data, 20.51%), generic word (29 data, 23.78%), additional explanation (3 data, 2,.47%), and footnote (3 data, 2.47%). The orientations of translation ideology were foreignization (translating 59 data – 48.39%) and domestication (translating 63 data – 61.51%). It can be concluded that the preservation of Javanese cultural lexicon is not optimally executed by the translator because the domestication slightly dominates the foreignization. However, the wide variety of applied translation strategies shows that translation practice is dynamic.